Multiple Myeloma - A hospital based cross sectional study in Bangladesh (Journal of the Asiatic Society of Bangladesh, Science, 2013)
Bone marrow morphological examination was performed on 835 patients either admitted in the inpatient departments of BIRDEM General Hospital or examined on outpatient basis. 760 of them were adults and 75 of them were children. 74 of the patients were diagnosed as suffering from a blood cancer known as Multiple Myeloma (MM). The age range of MM in our study was 40 to 85 years with a mean age of 63.25 years. Male to female ratio was 5:2 with a slight male preponderance. The median age of presentation was lower in females (60 years) than in males (65 years). MM was the second most frequent haematological disorder among all the patients examined, the most frequent one being leukemia. The frequency of MM was slightly higher among patients admitted in BIRDEM Hospital (10.4%) than those examined on outpatient basis (8.3%) although the difference was not statistically significant (P = 0.379 by Pearsons Chi square test). The highest frequency of MM was found in patients admitted in the department of Orthopaedic Surgery (20.8%) followed by the Department of Nephrology (16.7%). This data represents a cross sectional picture of the prevalence of MM in elderly population. DOI: http://dx.doi.org/10.3329/jasbs.v38i2.15609 J. Asiat. Soc. Bangladesh, Sci. 38(2): 189-198, December 2012